Analysis of the multicomponent magnetization of the Little Dal Group, Mackenzie Mountains, Northwest Territories, Canada (Dataset) ... - J. K. Park (Magnetics Information Consortium (MagIC), 2007)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Analysis of the multicomponent magnetization of the Little Dal Group, Mackenzie Mountains, Northwest Territories, Canada ...